Who adopts the Airbnb innovation? An analysis of international visitors to Western Australia - Volgger, Michael; Pforr, Christof; Stawinoga, A.; Taplin, Ross; Matthews, S. (Centre for Tourism Research and Development, 2018)
Airbnb is the most prominent example of novel peer-to-peer networks in tourism. This new form of accommodation provision may alter demand structures in tourism destinations and has led to uncertainty amongst established accommodation providers and destination marketers. To gain a better understanding of Airbnb adopters, this paper systematically compares actual travel behaviour of Airbnb users in a specific destination with that of visitors staying in traditional accommodation. Due to this controlled comparison, the paper is the first one to offer a robust comparative profiling of Airbnb users. The analysis is based on a logistic regression of data from the standardised International Visitor Survey for 2015 in Western Australia. Results indicate that Airbnb users in Western Australia differ from visitors staying in traditional accommodation, but that it might be wrong to conceive Airbnb adopters to be ‘alternative tourists’ beyond the mainstream.